2015
DOI: 10.1007/s00276-015-1483-y
|View full text |Cite
|
Sign up to set email alerts
|

Applied anatomical study of the modified anconeus flap approach

Abstract: The present study has demonstrated a new approach for adequately exposing the distal humeral articular surface during surgery for an intercondylar humerus fracture. With this modified approach, osteotomy of the olecranon and the separation or transection of the main part of the triceps brachial tendon from the olecranon are not necessarily required. Therefore, we suggest that this novel approach could be applied as the primary surgical approach in intercondylar humerus fracture surgeries if the surgeons are fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Continuity width was 16.8 mm (Keener et al, 2010). Although Sun et al (2015) did not report consistency of findings, Keener found the connection in all cases. Molinier et al (2011) failed to detect a linkage in 1 out of 30 elbows.…”
Section: /60mentioning
confidence: 76%
See 1 more Smart Citation
“…Continuity width was 16.8 mm (Keener et al, 2010). Although Sun et al (2015) did not report consistency of findings, Keener found the connection in all cases. Molinier et al (2011) failed to detect a linkage in 1 out of 30 elbows.…”
Section: /60mentioning
confidence: 76%
“…Triceps brachii-anconeus 3 (61) 50/51 Three studies (Keener et al, 2010;Molinier et al, 2011;Sun et al, 2015) reported that the lateral triceps brachii fused with the anconeus. Continuity width was 16.8 mm (Keener et al, 2010).…”
Section: /60mentioning
confidence: 99%
“…In an attempt to avoid denervation, O'Driscoll et al (2000) introduced the triceps reflecting anconeus pedicle approach as an inter-nervous plane approach. Sun et al (2015) also described a modification of this approach. Protection of the anconeus nerve is possible in many described approaches; however, surgeons must be aware of the exact position and topography of the nerve.…”
Section: Resultsmentioning
confidence: 99%
“…The precise anatomy of the anconeus nerve is an important subject for study, first to protect it during surgical approaches to the elbow (O'Driscoll, 2000;O ¨zer et al, 2005;Sun et al, 2015) and second because it may be a potential donor for transfer to other peripheral nerves of the upper extremity (Bertelli and Ghizoni, 2014;Bertelli et al, 2007). In the previous descriptions, we have not seen clear topographic relationships between the nerve and applicable bony landmarks, and therefore saw the necessity to review the course of the anconeus nerve.…”
Section: Introductionmentioning
confidence: 99%